1914
DOI: 10.1084/jem.19.5.459
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Serum Antitrypsin

Abstract: T h e e f f o r t s t h a t h a v e b e e n m a d e to d e t e r m i n e the n a t u r e o f the f e r m e n t -i n h i b i t i n g s u b s t a n c e s o f t h e b l o o d give n o definite i n f o r m at i o n c o n c e r n i n g t h e i r significance o r t h e i r c h a r a c t e r .A t one t i m e it w a s t h o u g h t t h a t the a n t i t r y p t i c Brieger and Trebing (z) stated that 9o per cent. of the patients suffering from carcinoma or sarcoma, whom they had examined, showed a n increase of antitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1915
1915
1976
1976

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Various investigators have been struck by the uniformity of the main manifestations of bacterial toxacmia in animals of the same species and have come to the conclusion that the symptoms are due not to specific bacterial endotoxins but to a non-specific poison formed (1) either from the bacteria themselves by the action on them of antibodies and complement (Teale and Embleton [1], Vaughan [2]); or (2) from the plasma of the infected animal (Jobling and Petersen [3]). These last authors believe that bacteria can adsorb antitrypsin and so allow the plasma proteolytic enzymes to give rise to proteose-like toxic bodies from the animal's own body fluids.…”
Section: Serum Antitrypsin and Autolysismentioning
confidence: 99%
“…Various investigators have been struck by the uniformity of the main manifestations of bacterial toxacmia in animals of the same species and have come to the conclusion that the symptoms are due not to specific bacterial endotoxins but to a non-specific poison formed (1) either from the bacteria themselves by the action on them of antibodies and complement (Teale and Embleton [1], Vaughan [2]); or (2) from the plasma of the infected animal (Jobling and Petersen [3]). These last authors believe that bacteria can adsorb antitrypsin and so allow the plasma proteolytic enzymes to give rise to proteose-like toxic bodies from the animal's own body fluids.…”
Section: Serum Antitrypsin and Autolysismentioning
confidence: 99%
“…In a previous paper we have shown that there is no element of specificity in so far as the proteases are concerned in the digestion occurring in the Abderhalden reaction (I3). The digest is obtained from the serum proteins and is brought about by changes in the colloidal state of dispersion of the serum induced by the antigen introduced as a substrate, resulting in what may be termed local areas of antiferment deficiency, due either to an actual adsorption of antiferment by a formed substance, such as a precipitate, or to a change in the degree of dispersion of the unsaturated lipoids upon which the antiferment property depends, as we have previously demonstrated (14). If a protease is present in such sera a positive reaction can occur; if not, the digestion does not take place.…”
Section: Non-specificity Of Serum Proteasementioning
confidence: 99%
“…Serum proteolytic inhibition was found to be increased in association with many diseases. Jobling and Petersen presented a comprehensive review of the subject in 1914 (2), and Grob reviewed the interval literature in 1942 (3). The physiological significance of proteolytic inhibition and the reasons for its increase with disease are not yet known.…”
Section: (From the Sloan-k Ettering Institute For Cancer Researck Anmentioning
confidence: 99%